The effect of extract of Punica granatum var. pleniflora for treatment of minor recurrent aphthous stomatitis - Shahin Gavanji; Behrouz Larki; Azizollah Bakhtari (Integrative Medicine Research)
Background: Herbal drugs are considered alternative agents and have been used for several years around the world. Recurrent aphthous stomatitis (RAS) is one of the most common problems recognized by dentists and skin specialists. This problem is characterized by recurring, painful, small oral mucosal ulcers with a round or oval aspect that mostly appear in keratinized mucosa, cheeks, and on the surface of the mouth under the tongue. Methods: In our experiment, the alcoholic and water extracts of Punica granatum var. pleniflora, P. granatum var. Sweet Alak, and P. granatum var. Saveh Black were tested on minor RAS. The study was carried out using the double-blind method. The study population consisted of 210 participants, of whom 69 were females (32%) and 141 were males (68%). In addition to checking several factors, the pain and the degree of the participant's satisfaction had been determined based on visual analog scale. Data analysis was done in the form of a nonparametric method using Kruskal–Wallis test and SPSS version 20 software. Results: The results show that the alcoholic and water extracts of P. granatum var. pleniflora have a meaningful therapeutic effect on minor RAS. Results from the antioxidant activity and its relation to total phenolics show that P. granatum var. pleniflora and P. granatum var. Sweet Alak are rich in phenols. Conclusion: The water and alcoholic extracts of P. granatum varpleniflora decreased the entire time of complete treatment, and the treatment was meaningfully satisfactory for patients who participated in this experiment.